Against all odds : Heroes of Quantico, Bk 1 - Hannon, Irene (Grand Rapids, MI : Revell, 2009)
For FBI hostage rescue team member Evan Cooper and his partner, dignitary protection duty should have been a piece of cake. Unfortunately, beautiful but determined Monica Callahan isn't making it easy...
Keywords: United States. -- Federal Bureau of Investigation -- Fiction; Government investigators -- Fiction; Love stories